“L’Università oggi: sfide e prospettive di sviluppo per l’università contemporanea” - Zani (Mons.), Angelo Vincenzo (Alpha Omega, 2015)
Summary: The article presents the magisterial lecture on the occasion of the inauguration of the Academic Year of the Pontifical Athenaeum Regina Apostolorum. In it, the author reflects on: “The University Today: Challenges and Perspectives for the Contemporary University”. The reflections are based on the Instrumentum laboris prepared by the Congregation for Catholic Education and entitled: “Education Today and Tomorrow. A Passion for Renewal”. Three points are considered: a) the reason for the document and how it was prepared; b) the principal content of the document; c) useful suggestions for Ecclesiastical Faculties.Key words: university, catholic education, ecclesiastical faculties, Holy See, instrumentum laboris, renewal of education.Parole chiave: università, educazione cattolica, facoltà ecclesiastiche, Santa Sede, instrumentum laboris, rinnovamento educativo.